2021
DOI: 10.1029/2020ms002385
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential of Deep Learning for Emulating Cloud Superparameterization in Climate Models With Real‐Geography Boundary Conditions

Abstract: Although global atmospheric model simulations are increasingly high-resolution, even under optimistic scenarios of enhanced computing performance, physically resolving the atmospheric turbulence controlling clouds will likely not be feasible for decades. Current climate model horizontal grid cells are typically 50-100 km wide but the turbulent updrafts governing cloud formation occur on scales of just tens to hundreds of meters and the microphysical processes regulating convection occur down at the micrometer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…We selected the global sub-grid heating and moistening fields at 700 hPa for the evaluation of the VAE's R 2 (Figure 3). We choose dq/dt and dT/dt fields at this pressure level because of the limited skill in fitting lower tropospheric convective processes with neural nets that has been reported across multiple investigations, and which has been speculated to be associated with an underrepresentation of stochastic variability linked to shallow and deep convection (Gentine et al (2018); ; Mooers et al (2021); Wang et al (2021)). Both networks, VAE and reference ANN, exhibit similar emulation skill patterns for heating and moistening tendencies, including the skill deficits for low-level moistening tendencies in the tropics, as seen in previous studies.…”
Section: Mean Regimes and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected the global sub-grid heating and moistening fields at 700 hPa for the evaluation of the VAE's R 2 (Figure 3). We choose dq/dt and dT/dt fields at this pressure level because of the limited skill in fitting lower tropospheric convective processes with neural nets that has been reported across multiple investigations, and which has been speculated to be associated with an underrepresentation of stochastic variability linked to shallow and deep convection (Gentine et al (2018); ; Mooers et al (2021); Wang et al (2021)). Both networks, VAE and reference ANN, exhibit similar emulation skill patterns for heating and moistening tendencies, including the skill deficits for low-level moistening tendencies in the tropics, as seen in previous studies.…”
Section: Mean Regimes and Statisticsmentioning
confidence: 99%
“…Similar advances in the prognostic skill, where the ML approach is coupled to the dynamical core of a circulation model, of global precipitation distributions on an aquaplanet were achieved by Yuval and O'Gorman (2020), with random forests and neural networks. Beyond aquaplanets, Mooers et al (2021) showed that feed-forward neural nets also skilfully reproduce the superparameterization (SP) in the presence of real topography based on offline tests, where the ML approach is evaluated against test data, without implementing the resulting representation back into the GCM. Han et al (2020) likewise demonstrated the potential to learn SP with residual neural nets based on real topography data.…”
Section: Introductionmentioning
confidence: 99%
“…This makes the ML training problem easier to precisely formulate, but also sidesteps important real‐world complications such as orography, land surface heterogeneity, complex coastlines, etc. Other studies have tackled real‐world geography but only demonstrated offline or single‐column ML skill (Han et al., 2020; Mooers et al., 2021). Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond aquaplanets, Mooers et al. (2021) showed that feed‐forward neural nets also skilfully reproduce the SuperParameterization (SP) in the presence of real topography based on offline tests, where the ML approach is evaluated against test data, without implementing the resulting representation back into the GCM. Han et al.…”
Section: Introductionmentioning
confidence: 99%
“…Similar advances in the prognostic skill, where the ML approach is coupled to the dynamical core of a circulation model, of global precipitation distributions on an aquaplanet were achieved by Yuval and O'Gorman (2020), with random forests and neural networks. Beyond aquaplanets, Mooers et al (2021) showed that feed-forward neural nets also skilfully reproduce the SuperParameterization (SP) in the presence of real topography based on offline tests, where the ML approach is evaluated against test data, without implementing the resulting representation back into the GCM. Han et al (2020) likewise demonstrated the potential to learn SP with residual neural nets based on real topography data.…”
mentioning
confidence: 99%